Dampak Pengembangan Pariwisata Terhadap Kondisi Ekonomi Dan Sosial Budaya Masyarakat Lokal Di Kawasan Pariwisata Sanur - Dinata, I Kadek Krisna Surya; Mertha, I Wayan; Sukariyanto, I Gede Made (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Sanur Tourism Area has experienced rapid development and has become an icon of tourism in Bali over the past 80 years. Strategic issues related to the development of Sanur’s tourism area concern economic and socio-cultural aspects. This research aims to identify the strongest impacts felt by the local community in the Sanur Tourism Area in the economic and socio-cultural dimensions. A quantitative approach was used, employing descriptive analysis. The sample was drawn through proportional purposive sampling with a total of 98 respondents. Data were collected through surveys using questionnaires, interviews, and documentation. The research findings indicate that the strongest positive economic impact perceived by the local community is an increase in job opportunities, while the most significant socio-cultural impact is an improvement in communication skills and foreign language proficiency. The community also experiences a high level of dependence on the tourism sector, and socially, there is a notable shift in lifestyle and consumption patterns toward imported products.